Effect of Production Method on the Mechanical Properties of Resin - Fiber S-GLASS Composite for the Rocket Nose Cone Application - Tarkono Tarkono; Sugiyanto Sugiyanto; Akhmad Riszal; Ignatius Bayu Atmoko; Fauzi Ibrahim; Joy Rizki Pangestu Djuansjah (Institut Teknologi Bandung, 2022)
Composite materials are increasingly developing in industrial advances both for everyday life or technological applications in industry. Composite material is a combination of two or more different components. Composite materials have certain physical and mechanical properties that are better than the properties of each of their constituent components. This research has been analyzed to determine the effect of the method of making fiber composites s-glass matrix resin 100 as material nose cone rocket rx-450 by using the method of hand lay up and vacuum infusion. Making a nose cone is carried out in several stages which are quite complicated, starting with preparation master mole for print beginning until polishing compound molding release on molding as finishing. The results obtained from this study are by using the method vacuum infusion lighter compared with material results method hand lay-up because on method vacuum infusion resin can be removed from the laminate. Whereas on method hand layup infiltration resin in fiber not enough perfect and administration of resin that cannot be controlled so that it can affect the mass from product composite.